Visualization of forward light scatter in opacified intraocular lenses and straylight assessment - Son, Hyeck Soo; Łabuz, Grzegorz; Khoramnia, Ramin; Yildirim, Timur Mert; Choi, Chul Y.; Knorz, Michael C.; Auffarth, Gerd U. (Diagnostics, 2021)
Background: Qualitative visualization of forward light scatter and quantitative straylight measurement of intraocular lenses (IOLs). Methods: We analyzed two calcified IOL-explants, the Euromaxx ALI313Y (Argonoptics GmbH) and the LS-312 MF30 (Oculentis BV), one IOL with artificially induced glistenings (PC-60AD, Hoya), and one control (CT Asphina 409MP, Carl Zeiss Meditec AG) free of any opacification. Analysis included light microscopy, qualitative light scatter visualization using ray propagation imaging technique, and quantitative straylight measurement using C-Quant (Oculus). Results: More light scattering effect-visible as increased light intensity outside the IOUs main focus-was evident in all opacified IOLs than the control. The highest straylight levels were observed in the Euromaxx (289.71 deg(2)/sr), which showed extensive granular deposits throughout its optic, followed by the MF30 (78.58 deg(2)/sr), which only showed opacification in its center. The glistenings-IOL demonstrated numerous microvacuoles within the optic and had straylight levels of 22.6 deg(2)/sr, while the control showed the lowest straylight levels (1.7 deg(2)/sr). Conclusions: Ray propagation imaging technique allowed qualitative assessment of off-axis veils of light that result from increased forward light scattering. Straylight was increased in all opacified lenses compared to the clear control lens. The IOL opacifications are significant sources of glare.
Gesehen am 30.09.2021